Gender impartiality of public institutions, religiosity, and satisfaction with democracy: findings from Turkey. Issue 2 (17th February 2022) - Sahin, Osman; Akboga, Sema
ABSTRACT: Previous literature demonstrated that gender inequality is a major challenge for democratic consolidation. However, research that studies the effect of gender inequality on citizens' satisfaction with democracy is limited. This study contributes to this literature by exploring the relationship between citizens' perceptions of gender impartiality of public institutions and satisfaction with democracy in Turkey, where gender inequality is an acute problem. Analysis of a nationally representative survey showed that the perception of gender impartiality of public institutions is a major factor explaining citizens' satisfaction with democracy. Results also revealed that perceptions of gender impartiality of public institutions affect citizens' evaluations of the long-term performance of democracy. Another finding is that religiosity moderates the effect of perceptions of gender impartiality of public institutions on citizens' satisfaction with democracy. We conclude that gender inequality is not a peripheral issue to democratic consolidation in Turkey but a social problem that remains at the heart of it.